2015
DOI: 10.18632/oncotarget.5293
|View full text |Cite
|
Sign up to set email alerts
|

EGFRvIII does not affect radiosensitivity with or without gefitinib treatment in glioblastoma cells

Abstract: BackgroundGlioblastomas (GBM) are often characterized by an elevated expression of the epidermal growth factor receptor variant III (EGFRvIII). We used GBM cell lines with native EGFRvIII expression to determine whether this EGFR variant affects radiosensitivity with or without EGFR targeting.MethodsExperiments were performed with GBM cell lines lacking (LN229, U87MG, U251, CAS-1) or endogenously expressing EGFRvIII (BS153, DKMG). The two latter cell lines were also used to establish sublines with a low (−) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 24 publications
7
34
0
Order By: Relevance
“…Interestingly, proliferation rate of the DK-MG high line in serum free media is trending to be higher than that of DK-MG low line, although statistical significance has not been reached. Those results find confirmation in the molecular studies, which show similar levels of PI3K/Akt signaling pathway activation in both DK-MG cell lines (Figure 4A-4D), pathway that is associated with the proliferation and survival processes, a result identical to the one observed by Struve and colleagues [55, 57, 58]. It should be noted that PI3K/Akt signaling pathway is often referred to as the main signal transducer of the EGFR vIII signaling, which is contradictory to our data [6, 22, 41, 59].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Interestingly, proliferation rate of the DK-MG high line in serum free media is trending to be higher than that of DK-MG low line, although statistical significance has not been reached. Those results find confirmation in the molecular studies, which show similar levels of PI3K/Akt signaling pathway activation in both DK-MG cell lines (Figure 4A-4D), pathway that is associated with the proliferation and survival processes, a result identical to the one observed by Struve and colleagues [55, 57, 58]. It should be noted that PI3K/Akt signaling pathway is often referred to as the main signal transducer of the EGFR vIII signaling, which is contradictory to our data [6, 22, 41, 59].…”
Section: Discussionsupporting
confidence: 85%
“…Of particular importance is the fact that EGFR vIII mRNA levels as well as amplicon number did not change over prolonged culturing periods (Sup.Figure 6), even though loss of EGFR vIII amplicons during in vitro adaptation process of primary tumor cells has been observed by us (Figure 1C) and consistently reported in the literature [26, 27]. Stability of the DK-MG line, also confirmed by Struve and colleagues [55], is of particular importance in scientific research and drug development, where model's stability is a basic requirement.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Camorani and colleagues [31] reported that aptamers could target EGFRvIII and affect the migration, invasion, and proliferation of GBM cells by hampering the constitutive autophosphorylation of EGFRvIII. Struve and colleagues [32] performed experiments to confirm that EGFRvIII did not alter radiosensitivity with or without gefitinib during anti-EGFR treatment in glioblastoma cells. However, these two studies both focused on uniform populations of EGFRvIII-expressing cancer cells, and surrounding cells were not taken into account.…”
Section: Discussionmentioning
confidence: 99%